Parliamentary government in Southern Asia. An introductory essay on developments in Burma, Ceylon, India, and Pakistan, 1947-1952. [Forew. by W.L. Holland (Hansard Society, 1953)
With index. Issued in co-operation with the International Secretariat, Institute of Pacific Relations.